If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.04x + 3(3000 + -1x) = 0 0.04x + (3000 * 3 + -1x * 3) = 0 0.04x + (9000 + -3x) = 0 Reorder the terms: 9000 + 0.04x + -3x = 0 Combine like terms: 0.04x + -3x = -2.96x 9000 + -2.96x = 0 Solving 9000 + -2.96x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9000' to each side of the equation. 9000 + -9000 + -2.96x = 0 + -9000 Combine like terms: 9000 + -9000 = 0 0 + -2.96x = 0 + -9000 -2.96x = 0 + -9000 Combine like terms: 0 + -9000 = -9000 -2.96x = -9000 Divide each side by '-2.96'. x = 3040.540541 Simplifying x = 3040.540541
| (25*0)+(15*y)=30500 | | T=x-6 | | 6z+0.36=24072 | | t+0.9=9 | | 2(x-1)+3(3x+4)=4 | | e^14x=110 | | h=-16t^2+24t | | 0.007x^2+0.02x-150=0 | | 2x^2+8x-15= | | 9z+5=11z-5 | | 10-4r=-2(3r+5)+7r | | 2x-x+6x+5=41 | | 5(-4)=-3x+44 | | -6(10+p)=-150 | | 20x-x^2-150=0 | | 10+6x-4=26+2x | | -7w+4=10 | | 8x+24+2x+96=180 | | -2n+4n-7=0 | | -12+x=-3 | | 3y-6=6(y-2) | | -5-4x-2x=-7 | | 12+3x-3=15-4x | | (12x^2)+x+4=0 | | 3(5x-7)=5(3x+4) | | 3x+6x-6=18 | | 4x+4+2x+38=180 | | 4z-13=3 | | 2x+4=5(x+1)3-(x+2) | | 12x^4=18x^2 | | x-9y+7=0 | | 7x+2x-7=3 |